Effect of a Rapid Response Team on the Incidence of In-Hospital Mortality. Issue 1 (22nd March 2023) - Factora, F.; Maheshwari, K.; Khanna, S.; Chahar, P.; Ritchey, M.; O'Hara, J.; Mascha, E.J.; Mi, J.; Halvorson, S.; Turan, A.; Ruetzler, K.
Abstract : ( Anesth Analg . 2022;135:595–604) Cardiopulmonary arrest in-hospital leads to increased mortality yet is largely preventable with signs of deterioration prior to serious and emergent changes in patients. To intervene early when clinical deterioration is evident prior to adverse effects of cardiopulmonary arrest, rapid response teams (RRTs) were introduced. A nurse-led RRT was introduced in 2009 at a large tertiary medical center, which switched to being anesthesiology-led in 2012. This study primarily aims to compare in-hospital mortality with RRT initiation (2005-2008 vs. 2009-2018). It also aims to compare in-hospital mortality with policy changes following the initiation of an anesthesiology-led RRT.